Pretrial Release Conditions in Domestic Violence Cases: Issues and Context (2006) - Jane M. Sadusky (My University, 2016)
This paper explores the issues related to pretrial release, highlights the experiences of several communities that have been puzzling over these questions, and provides guidelines to communities for examining this aspect of criminal case processing in domestic assault cases.